Industry 4.0 and Society 5.0: comparative views (Research, Society and Development, 2021)
Organizations have been introduced to a new form of productive organization, called Industry 4.0, with the promise of integrating their processes, high customization, high production and reduced production costs. Based on the concepts of Industry 4.0, several variations emerged, such as Logistics 4.0, Health 4.0, and Agriculture 4.0. However, it was in Japan that the idea Society 5.0 emerged, which promises the application of all aspects of the fourth revolution and its consequences in a fully autonomous society. The present work compares Industry 4.0 and Society 5.0 in relation to origin, structuring elements and use of technology. The methodology used was a bibliographical research. The result presents a list of 10 characteristics that compare the year of creation of the concept, country of origin, motivating need, level of urgency, focus, scope of application, use of technology, degree of use of artificial intelligence, fundamental elements and developments from the concept. Contributions to the practice are based on the establishment of differences that can contribute so that strategists, investors and production managers can understand the differences and envision a near future.